High uric acid promotes dysfunction in pancreatic β cells by blocking IRS2/AKT signalling. (15th January 2021) - Hu, Yaqiu; Zhao, Hairong; Lu, Jiaming; Xie, De; Wang, Qiang; Huang, Tianliang; Xin, Hancheng; Hisatome, Ichiro; Yamamoto, Tetsuya; Wang, Wei; Cheng, Jidong
Abstract: Hyperuricaemia is a disorder of purine metabolism. Elevated serum uric acid is strongly associated with many diseases, including gout, abdominal obesity, insulin resistance, and cardiovascular and kidney disease. Our previous studies showed that high uric acid (HUA) induced insulin resistance in several peripheral organs, including the liver, myocardium and adipose tissue. However, whether HUA directly induces insulin resistance of pancreatic β cells, the only source of insulin in the body and also a sensitive insulin target, is unknown. In this study, pancreatic β cells pretreated with HUA showed impaired insulin expression/secretion, glucose uptake and the glycolytic pathway. RNA-seq revealed that HUA affected the biological processes of INS-1 cells broadly, including oxidoreduction coenzyme metabolic process, pyruvate metabolic process, and glycolytic process. In addition, HUA reduced mitochondrial membrane potential and increased the production of reactive oxygen species(ROS) in INS-1 cells. INS-1 cells pretreated with probenecid, an organic anion transporter inhibitor, protected INS-1 cells against HUA-induced insulin secretion decrease, Pretreatment with N-acetyl-L-cysteine(NAC), a globally used antioxidant, recovered HUA-decreased insulin secretion and glucose uptake by pancreatic β cells. Insulin-like growth factor 1 (IGF-1), the phosphatidylinositol 3-kinase (PI3K) activator, rescues HUA-decreased insulin secretion by re-activating AKT phosphorylation. Thus, HUA induce insulin resistance, impaired insulin secretion and glycolytic pathway of pancreatic ꞵ cell through IRS2/AKT pathway. Highlights: Insulin secretion disorder was found in mice with acute hyperuricemia. High uric acid (HUA) impairs glycolytic pathway, and causes early apoptosis in pancreatic β cells. Pre-treatment with antioxidant (NAC) and insulin-like growth factor 1 (IGF-1) could recover HUA-decreased insulin secretion and glucose uptake by pancreatic β cells. HUA blocks IRS2/AKT signalling.